STRATEGY FOR INCREASING COMPETITIVENESS IN THE INDUSTRY 4.0 ERA THROUGH DIGITALIZATION OF MSME BOOKKEEPING - Trinandari Nugrahanti; Djoko Hanantijo; Agus Salim (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
Community service was conducted in Desa Jambudipa, Kabupaten Bandung Barat, aiming to improve the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) hindered by weak financial management and low digital literacy. The program employed the Asset-Based Community Development (ABCD) approach through participatory training and mentorship stages. Data were collected via observation, interviews, and pre- and post-training assessments, then analyzed using descriptive statistics and correlation analysis. Results showed a significant improvement in participants' digital bookkeeping skills and financial management understanding, with a positive correlation between digital adoption and business performance (r=0.67, p<0.05). The program transformed traditional bookkeeping into a transparent, efficient, sustainable digital system. This asset-based model has the potential to be replicated in other rural communities.